1959
DOI: 10.1111/j.1365-246x.1959.tb05790.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Processes of Abyssal Sedimentation: Erosion, Transportation, and Redeposition on the Deep-sea floor

Abstract: The concept of a quiet, nearly motionless, and certainly currentless deep-sea floor lacking the processes of erosion so prevalent in shallower seas was well ingrained in scientific thought until discoveries of the past decade revised this serene and static picture. The new concept is a more dynamic one in which submarine landslides, raging turbidity currents, internal tides, deep-sea current scour, and submarine postdepositional solution and alteration play a part in shaping the sea floor, in disturbing and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1961
1961
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Heezen 1959;Heezen & Johnson 1963;Hubert 1964). Finally, it was the compilation of evidence by Heezen et al (1966) on Shaping of the continental rise by deep geostrophic contour currents that caught the imagination of many more geologists. Stow & Lovell (1979) suggested that this paper marked the beginning of a revolution in sedimentology comparable to the turbidite revolution.…”
Section: Contouritesmentioning
confidence: 99%
See 1 more Smart Citation
“…Heezen 1959;Heezen & Johnson 1963;Hubert 1964). Finally, it was the compilation of evidence by Heezen et al (1966) on Shaping of the continental rise by deep geostrophic contour currents that caught the imagination of many more geologists. Stow & Lovell (1979) suggested that this paper marked the beginning of a revolution in sedimentology comparable to the turbidite revolution.…”
Section: Contouritesmentioning
confidence: 99%
“…Marine geologists were documenting many other kinds of evidence that indicated an important role for bottom currents flowing alongslope in deep water (e.g. Heezen 1959;Heezen & Johnson 1963;Hubert 1964). Finally, it was the compilation of evidence by Heezen et al (1966) on Shaping of the continental rise by deep geostrophic contour currents that caught the imagination of many more geologists.…”
Section: Contouritesmentioning
confidence: 99%
“…Piston cores collected by the Lamont-Doherty Geological Observatory, and cores drilled on Legs 1 and 11 of the JOIDES Deep-Sea Drilling project (JOIDES, 1968(JOIDES, , 1970 in the western North Atlantic, contain middle and lowermost Cretaceous sediments rich in unoxidized organic clays, JOIDES Core 105 (from Leg 11, 1970) includes a sequence of Lower Cretaceous clays so rich in carbonaceous material that some samples will actually burn (JOIDES, 1970). The present-day Red Sea, then, appears to be not only a tectonic analog to the proto-Atlantic (Heezen, 1960), but a sedimentary analog as well.…”
Section: Red Sea Stagementioning
confidence: 99%
“…Since introduction of the theory of ocean basins widening by growth of new crust at the mid-ocean ridges (Heezen, 1959;Hess, 1962;Dietz, 1961), exciting new findings have been presented describing: (1) rates of sea-floor spreading using sea-floor magnetic data (Vine and Mathews, 1963;Heirtzler and others, 1968); (2) ages of prominent seismic reflectors within the ocean floor (Ewing and others, 1966); and (3) deep-ocean sedimentary processes (Heezen and others, 1966;Schneider and others, 1967). With this background, one can attempt to reconstruct the history of sedimentation in a widening and deepening ocean environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation